Latest updates on chronic delta hepatitis - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2016)
The hepatitis D virus was shown for the first time in 1977 by Rizzetto and friends. The HDV genome and the cloning of sequence were made in 1986. HDV is the first animal virus with circular RNA genome which is seen only in plant viruses. HDV is an RNA virus with the known smallest viral genome in animal viruses. It is classified as Deltavirus genius depending on the type of virus by ICTV in 1996. HDV is classified as the sole example of delta virus in this genus. Chronic delta hepatitis is the least common form of chronic viral hepatitis due to hepatotropic viruses. In contrast, the virus is highly pathogenic and can cause serious consequences. Today, prevalance of delta hepatitis has been shown to decrease. However, the delta hepatitis continues to be an important health problem in some parts of the world. In our country, especially in Eastern and Southeastern Anatolia, hepatitis D is a serious and important health problem and still maintains its importance as a health problem. In Turkey, still there is a significant number of patients with HDV infection despite a documented decrease in HDV infection. The recommended treatment for chronic HDV infection in the current guidelines is the treatment with peginterferon alfa given once a week for 48 weeks. Treatment is indicated for patients who has compensated disease with active infection. In patients with advanced form of disease, the expected benefits of the peginterferon must be well balanced against the potential side effects and low response rate. An oral antiviral can be recommended in patients who has high levels of serum HBV DNA. In contrast, the control of HBV infecion does not seem to change the natural history of HDV related disease.
Keywords: Delta hepatitis; Treatment; Prognosis; VIRUS HDV INFECTION; B-VIRUS; INTERFERON THERAPY; LIVER-TRANSPLANTATION; GENETIC-VARIABILITY; RNA; CIRRHOSIS; PREVALENCE; EFFICACY; DISEASE